SISTEM INFORMASI PENGOLAHAN DATA OPERASIONAL PADA GMC FUTSAL JAMBI - Novri Adhiatma (JURNAL AKADEMIKA)
GMC (Gunung Manahan City) is an enterprise engaged in the field of sport. It faces the challenge of improving the quality of service for customers. The system used in the process of leasing the field on GMC Futsal still using manual systems, using paper media as a means pengimputan and storing data so that if necessary the data, it will take quite a long time to look for it and allow the duplication of data that can hinder the process of service to pelangan. From the problems above, an application designed to solve the problems. Operational Data Processing Information Systems In Futsal Gmc Jambi using the programming language Visual Basic 6.0 and My SQL. Information Systems data processing Futsal Field, is expected to address the issue in court bookings, scheduling arrangements and process customer transactions. So that arrangements can be done centrally and simplify the management stages of the collected data.